Placental Abruption with Couvelaire Uterus in a Primigravida: A Case Report - Immanuel Bachtiar Parlindungan; Dadan Susandi; Windi Nurdiawan; Hadi Susiarno; Aisyah Shofiatun Nisa (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Placental abruption typically presents with the classic triad of vaginal bleeding, abdominal pain, and uterine tenderness. However, atypical presentations lacking these features may delay diagnosis. The occurrence of an extensive couvelaire uterus requiring a hysterectomy in a young primigravida without classical risk factors is rare. This case adds to the limited literature on severe, atypical presentations of placental abruption.Case Illustration: A 20-year-old primigravida at 32 – 33 weeks of gestation presented with decreased fetal movements, lacking vaginal bleeding or significant abdominal pain. Notably, she reported a recent history of traditional abdominal massage. She was diagnosed with intrauterine fetal death (IUFD), and ultrasonography demonstrated a retroplacental hemorrhage suggestive of placental abruption. Despite the absence of classic symptoms, clinical suspicion remained high. Due to concerns of ongoing concealed hemorrhage and impending maternal deterioration, an emergency cesarean section was performed. Intraoperatively, a couvelaire uterus involving approximately 60% of the anterior uterine wall was identified. Following delivery, the patient developed refractory uterine atony unresponsive to uterotonics (oxytocin, methylergometrine, and misoprostol), necessitating a supravaginal hysterectomy to control life-threatening hemorrhage. The patient recovered well postoperatively.Conclusion: This case highlights an atypical presentation of placental abruption that progressed to severe maternal complications, including a couvelaire uterus and refractory atony requiring surgical intervention. Early recognition based on clinical suspicion and imaging is essential to prevent maternal morbidity when classical symptoms are absent. While the patient had a history of traditional abdominal massage, a definitive causal relationship cannot be established; further research is needed to explore its potential role as a trigger.Solusio Plasenta dengan Uterus Couvelaire pada Primigravida: Sebuah Laporan KasusAbstrakPendahuluan: Solusio plasenta umumnya bermanifestasi dengan triad klasik berupa perdarahan pervaginam, nyeri abdomen, dan nyeri tekan uterus. Namun, presentasi atipikal tanpa gejala tersebut dapat menyebabkan keterlambatan diagnosis. Kejadian uterus couvelaire luas yang memerlukan histerektomi pada primigravida muda tanpa faktor risiko klasik merupakan kondisi yang jarang dan menambah keterbatasan literatur mengenai presentasi berat solusio plasenta yang atipikal.Ilustrasi Kasus: Seorang wanita berusia 20 tahun, primigravida dengan usia kehamilan 32 – 33 minggu, datang dengan keluhan penurunan gerak janin tanpa disertai perdarahan pervaginam maupun nyeri abdomen bermakna. Pasien didiagnosis dengan intrauterine fetal death (IUFD). Pemeriksaan ultrasonografi menunjukkan adanya perdarahan retroplasenta yang mengarah pada solusio plasenta. Meskipun tanpa gejala klasik, kecurigaan klinis tetap tinggi berdasarkan temuan kematian janin dan hasil pencitraan, dengan pertimbangan adanya perdarahan tersembunyi yang sedang berlangsung serta risiko perburukan kondisi maternal. Selanjutnya, dilakukan seksio sesarea emergensi terhadap pasien. Secara intraoperatif ditemukan uterus couvelaire yang melibatkan sekitar 60% dinding anterior uterus. Setelah persalinan, pasien mengalami atonia uteri refrakter yang tidak responsif terhadap terapi uterotonik (oksitosin, metilergometrin, dan misoprostol) sehingga dilakukan histerektomi supravaginal untuk mengendalikan perdarahan yang mengancam jiwa. Pasien menunjukkan perbaikan klinis yang baik pascaoperasi.Kesimpulan: Kasus ini menyoroti presentasi atipikal solusio plasenta tanpa triad klasik yang dapat berkembang menjadi komplikasi maternal berat, termasuk uterus couvelaire dan atonia uteri refrakter yang memerlukan histerektomi. Pengenalan dini berdasarkan kecurigaan klinis dan temuan pencitraan sangat penting untuk mencegah morbiditas maternal. Meskipun pasien memiliki riwayat pijat abdomen tradisional, hubungan kausal tidak dapat dipastikan; diperlukan penelitian lebih lanjut untuk mengeksplorasi kemungkinan perannya.